Proteomic Analysis of Stationary Growth Stage Adaptation and Nutritional Deficiency Response of Brucella abortus - Yang, Jianghua; Liu, Mengzhi; Liu, Jinling; Liu, Baoshan; He, Chuanyu; Chen, Zeliang (Frontiers in Microbiology, 2020)
Brucellosis, an important bacterial zoonosis caused by Brucella species, has drawn increasing attention worldwide. As an intracellular pathogen, the ability of Brucella to deal with stress within the host cell is closely related to its virulence. Due to the similarity between the survival pressure on Brucella within host cells and that during the stationary phase, a label-free proteomics approach was used to study the adaptive response of B. abortus in the stationary stage to reveal the possible intracellular adaptation mechanism in this study. A total of 182 downregulated and 140 upregulated proteins were found in the stationary-phase B. abortus. B. abortus adapted to adverse environmental changes by regulating virulence, reproduction, transcription, translation, stress response, and energy production. In addition, both exponential and stationary-phase B. abortus were treated with short-term starvation. The exponential B. abortus restricted cell reproduction and energy utilization and enhanced material transport in response to nutritional stress. Compared to the exponential-phase, stationary Brucella adjusted their protein expression to a lesser extent under starvation. Therefore, B. abortus in the two growth stages significantly differed in the regulation of protein expression in response to the same stress. Overall, we outlined the adaptive mechanisms that B. abortus may employ during growth and compared the differences between exponential and stationary-phase B. abortus in response to starvation.